The Imposition of Penalties toward Drivers Transporting Timber Belonging to Business Actors (Study of Judge Decision Number 284/Pid.B/LH/2021/PN RBI) - Ridwan; Andriadin; Didik Irawansyah (Jurnal Jurisprudence, 2022)
ABSTRACT Purpose of the study: This article aimed to find out the legal facts in the case of transporting timber by the defendant (truck driver) (Judge Decision Study Number 284/Pid.B/LH/2021/PN RBI) and to understand the basics of the judge’s considerations in imposing a criminal sentence on the driver of the timber carrier belonging to the business actor.  Methodology: Legal-normative, statutory, and conceptual approaches; types of data in the form of primary and secondary data. Results : First, the legal facts show that in the case of the defendant (truck driver) transporting timber, there was coercion by business actors on the defendant (truck driver), and even the process of arrest was carried out by the police, as stated in the Raba Bima District Court decision number 284/Pid.B/LH/2021/PN denotes illegal arrest and detention according to the applicable laws and regulations. Second, after careful consideration, the judge imposed a criminal sentence on the defendant (truck driver) because there was no error in personal on the defendant and the fulfillment of the elements of every person, intentional transport of timber as referred to in Law Number 18 of 2013 concerning prevention, eradication, and destruction of forests, and participation in committing criminal acts as referred to in Article 55, paragraph 1 of the Criminal Code. But in this case, the judge did not carefully examine, understand, and interpret the element of participation in committing a criminal act so the judge's decision was deemed wrong neither theoretically nor practically. Applications of this study: It is expected that this research will add insight and knowledge to the community if they experience a similar incident as the Raba Bima District Court Decision 284/Pid.B/LH/2021/PN RBI. Additionally, this research is also expected to provide theoretically and practically benefits for law enforcement and the development of science and special research on aspects of criminal law. Novelty/Originalty of this study: From this research, no one has conducted a study specifically related to the judge's decision to punish the driver, in which the driver was coerced by the owner to transport his timber. Keywords: Criminal act; Judge’s Decision; Timber Transportation   ABSTRAK   Tujuan: Artikel ini bertujuan untuk mengetahui fakta hukum dalam perkara pengangkutan kayu oleh terdakwa (supir truk) dalam Kajian Putusan Hakim Nomor 284/Pid.B/LH/2021/PN RBI dan memahami dasar-dasarnya pertimbangan hakim dalam menjatuhkan pidana terhadap pengemudi pengangkut kayu milik pelaku usaha.  Metodologi: Pendekatan hukum-normatif, perundang-undangan, dan konseptual dengan jenis data berupa data primer dan sekunder.  Hasil : Pertama, fakta hukum menunjukkan bahwa dalam hal terdakwa (supir truk) mengangkut kayu, terjadi pemaksaan pelaku usaha terhadap terdakwa. Bahkan proses penangkapan dilakukan oleh pihak kepolisian, sebagaimana disebutkan dalam putusan Pengadilan Negeri Raba Bima nomor 284/Pid.B/LH/2021/PN merupakan penangkapan dan penahanan yang tidak sah menurut peraturan perundang-undangan yang berlaku. Kedua, setelah melalui pertimbangan yang matang, hakim menjatuhkan pidana kepada terdakwa (sopir truk) karena tidak ada kesalahan pribadi pada terdakwa dan terpenuhinya unsur setiap orang, pengangkutan kayu dengan sengaja sebagaimana dimaksud dalam Undang-Undang Nomor 18 Tahun 2013 tentang pencegahan, pembasmian, dan perusakan hutan, serta ikut serta melakukan tindak pidana sebagaimana dimaksud dalam Pasal 55 ayat 1 KUHP. Namun dalam hal ini hakim kurang teliti dalam mengkaji, memahami, dan menafsirkan unsur ikut serta melakukan tindak pidana sehingga putusan hakim dianggap salah baik secara teoritis maupun praktis.  Aplikasi penelitian ini: Diharapkan penelitian ini dapat menambah wawasan dan pengetahuan masyarakat jika mengalami kejadian serupa seperti Putusan Pengadilan Negeri Raba Bima 284/Pid.B/LH/2021/PN RBI. Selain itu, penelitian ini juga diharapkan dapat memberikan manfaat secara teoritis dan praktis bagi penegakan hukum dan pengembangan ilmu pengetahuan serta penelitian khusus pada aspek hukum pidana.  Kebaruan/Orisinalitas: Dari penelitian ini, belum ada yang melakukan penelitian secara khusus terkait dengan putusan hakim yang menghukum pengemudi, dimana pengemudi dipaksa oleh pemilik untuk mengangkut kayunya.  Kata Kunci: Tindak Pidana; Putusan Hakim; Transportasi Kayu